Fundamental Rights in the AFSJ: Strenthening or impediment? - Cuc, Nguyen Thi Kim (Pécs journal of international and European law, 2024)
The Area of Freedom, Security and Justice was created with the entry into force of the 1997 Amsterdam Treaty. This Area, ten years later, has been improved when the 2007 Lisbon Treaty amended the Treaty Establishing the European Community and renamed it the Treaty on the Functioning of the European Union. The Area of Freedom, Security and Justice (AFSJ) is an extensive field of law covering many policies and there is hence an increased risk for fundamen- tal rights violations. To describe the relevance of the protection of fundamen- tal rights within this Area as well as evaluate the effectiveness of fundamental rights, by using the polemic-critical method and analytical-logical method, this paper will focus on the scope of fundamental rights in some of the EU human rights instruments and the scope of these rights and freedoms in the AFSJ. As a result, this paper will answer the question related to the strengthening or imped- iment of fundamental rights as well as the balance between personal rights and collective interests such as security.